2019
DOI: 10.21608/ejhc.2019.62563
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge and Practices regarding to Fever Management of Neonates

Abstract: Background: Nurses in Neonatal Intensive Care Unit operate in a challenging environment with the demands of care of the infant and providing family-centered care. Aim of the Study: The present study aimed to assess nurses' knowledge and practice regarding to fever management of neonates. Study Design: A descriptive exploratory study design was utilized. Setting: The study was carried out at the neonatal intensive care units in Benisuef General Hospital, Benisuef Health Insurance Hospital affiliated to Ministry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
4
1
0
Order By: Relevance
“…This may be due to that all nurses had misconceptions about fever and the hospitals did not provide them with needed supplies. This result was consistent with Gouda et al, (2019) who found that two thirds of studied nurses had incompetent level of practice. Also, this result was supported with Khalifa (2007) who reported that incorrect practices related to fever management was recorded.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to that all nurses had misconceptions about fever and the hospitals did not provide them with needed supplies. This result was consistent with Gouda et al, (2019) who found that two thirds of studied nurses had incompetent level of practice. Also, this result was supported with Khalifa (2007) who reported that incorrect practices related to fever management was recorded.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study showed that two thirds of nurses had unsatisfactory knowledge about fever in children. This finding agreed with Gouda et al, (2019) who conducted a study about "Nurses' knowledge and practices regarding to fever management of neonates". They indicated that the majority of nurses had unsatisfactory knowledge regarding to fever management of neonates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concerning years of experience, the results of study under hand incongruent with study that carried out by quantitative cross-sectional survey to investigate fever management practices among physicians and nurses in Hebron district, who found that majority of participant has experience above 15 Years with 28% (5) . The findings of the study not in the same line with study that conducted in Egypt (6) aimed to assess nurses' knowledge and practice regarding to fever management of neonates. Who found that majority of sample not participation in training course.…”
Section: -Sociodemographic Characteristics Of the Samplesupporting
confidence: 51%
“…The care of patients with fever occupies a considerable amount of time for many nurses. But despite this extensive experience with fever, there are even healthcare professionals have misconceptions about the adverse effects of a fever and about when and how a fever should treat (Gouda et al, 2019). Fever can be a diagnostic challenge for health care professionals in patient at intensive care unit because it is often difficult to identify the cause (National Institute of Health, 2020).…”
Section: Significance Of the Studymentioning
confidence: 99%